Study of solid state interactions in the systems ZnFe2O4 – CaO, ZnFe2O4 – MgO and zinc cake with CaO and MgO - Boyanov, Boyan; Peltekov, Alexander (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
The solid state interactions of CaO and MgO with synthetic and industrial ZnFe2O4 (in zinc cake) have been studied using chemical, XRD analysis and Mössbauer spectroscopy. The exchange reactions in the systems ZnFe2O4 - CaO and ZnFe2O4 - MgO have been investigated in the range of 850–1200 oC and duration up to 180 min. It has been established that Ca2+ and Mg2+ ions exchange Zn2+ in ferrite partially and the solubility of zinc in a 7% sulfuric acid solution increases. The possibilities for utilization of the obtained results in zinc hydrometallurgy have been discussed.